Pengaruh Pendekatan Pembelajaran dan Kecerdasan Sosial terhadap Hasil Belajar PKn Di SMP - Linda Zakiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2014)
This research aims to reveal the effect of learning approach and social intel- ligences on learning outputs of civic education. It uses experimental quation methodes. The research was conducted at SMPN 154 and SMPN 139 Jakarta with 36 students. Group were selected cluster random sampling. Data analyzed with two-way analysis of variance (anova) and followed by Tuckey’s test. The results indicate: (1) learning outputs of contex- tual learning higher than conventional learning; (2) there is an interaction effect of learn- ing approach and social inteligences level on the learning outputs of civic education; (3) contextual learning approach brings higher learning outputs to the students group of higher social inteligence; and (4) conventional learning approach brings higher learning outputs to the students group of lower social inteligence.